(untitled) (IJM: Journal of Multidisiplinary, 2025)
This study aims to analyze the influence of work discipline and job satisfaction on employee performance at Century21 Metro Harapan Indah Bekasi, both simultaneously and partially. The research employs a quantitative approach using a saturated sampling method, in which the entire population of 72 employees was used as respondents. Data were collected through questionnaires that had been tested for validity and reliability, and subsequently analyzed using SPSS version 26 with multiple linear regression analysis. The results indicate that the work discipline variable has a positive and significant effect on employee performance. This finding suggests that the higher the level of employee discipline in adhering to organizational rules and responsibilities, the better their performance outcomes. Furthermore, job satisfaction also shows a positive and significant effect on employee performance, implying that employees who are satisfied with their work environment, reward system, and interpersonal relationships tend to exhibit higher motivation and stronger commitment to their tasks. In addition, the F-test results demonstrate that work discipline and job satisfaction simultaneously have a significant effect on employee performance, indicating that both factors play an essential role in fostering optimal performance within the workplace of Century21 Metro Harapan Indah Bekasi.